First order convergence of Milstein schemes for McKean-Vlasov equations and interacting particle systems - Bao, J; Reisinger, C; Ren, P; Stockinger, W (The Royal Society, 2021)
In this paper, we derive fully implementable first order time-stepping schemes for McKean–Vlasov stochastic differential equations (McKean–Vlasov SDEs), allowing for a drift term with super-linear growth in the state component. We propose Milstein schemes for a time-discretised interacting particle system associated with the McKean–Vlasov equation and prove strong convergence of order 1 and moment stability, taming the drift if only a one-sided Lipschitz condition holds. To derive our main results on strong convergence rates, we make use of calculus on the space of probability measures with finite second order moments. In addition, numerical examples are presented which support our theoretical findings.